Consciência ambiental como instrumento de efetivação da dignidade humana no sistema prisional - Caetano, Eduardo Paixão (2017)
The Brazilian prison system lives in inhuman and precarious conditions, with increasing overcrowding, which shows that the values of environmental law are far from being respected. It is also true affront to the dignity of the human person and this can be faced by Environmental Law with quick and viable solutions. It is not enough just to build new prisons, there is a need to go further, changing the conduct inside prisons, guaranteeing the prisoner a favorable environment, as guaranteed by law. Thus, these lines propose a systematic analysis of the prison environment in Brazil and the improvement in the treatment of the victims, allowing their full resocialization in a sustainable and adequate environment, even considering the effective privatization of the ruined public prisons, since the only thing That man loses when he is condemned is freedom, but never his dignity as a human being. The methodology used is the study of the current legislation, texts of the internet and, in addition, are used as source of research doctrines that deal with Environmental Law and its specific principles, as well as judged, whose decisions are based on them. Keywords: Human dignity, Overcrowding, Privatization, Minimal living floor.